Jordan v Farber (1352/09) 2009 ZANCHC 81 (15/12/2009) - Barnard, Jacolien; Nagel, Chris (Potchefstroom Electronic Law Journal, 2017)
This case note deals with several aspects of the law of contract, such as public policy and validity, error, cancellation, repudiation, undue influence and damages. It concerns the case of an elderly couple who had to stop their farming operations because of ill health. The attorney whom they approached for assistance offered to lease the farm, equipment and animals from them in his personal capacity, although in his professional capacity he also drafted the contracts of lease. It later transpired that the attorney used his position to mislead the couple as regards the contracts in question and that he was guilty of unethical and unprofessional conduct. The couple applied to court to have the leases declared void, alternatively cancelled, and to have the attorney evicted from the farm. The order was granted; however, the discussion seeks to demonstrate that the couple were afforded only minimal justice in that they did not claim, nor were they granted, any damages. The various possibilities open to them in the circumstances are examined and the conclusion is that ventilating the matter by way of application was probably not the best manner in which to have sought assistance.